ANALYSIS OF HUMOR AND HUMOROUS IMAGERY IN ELEANOR H. PORTER'S “MISS BILLY” (International journal of medical sciences, 2025)
This study explores the use of humor and humorous imagery in Miss Billy by Eleanor H. Porter. It examines how Porter employs comedic elements, character contrast, and social-domestic settings to enrich narrative, convey moral values, and shape readers’ emotional involvement. The analysis highlights the novel’s strengths — its vivid characterizations, effective humor, and social-class representation — while also addressing potential weaknesses, such as the protagonist’s inconsistent emotional decisions.